2016
DOI: 10.1556/650.2016.30610
|View full text |Cite
|
Sign up to set email alerts
|

A melanoma malignum korai felismerését befolyásoló tényezők

Abstract: Bevezetés és célkitűzés:A melanoma malignum igen agresszív, sokszor kiszámíthatatlan kórlefolyású daganat. Vizsgála-tunk során arra kerestünk választ, hogy milyen tényezők befolyásolják a betegség korai felismerését. Módszer: 139 melanomával diagnosztizált beteg kérdőíveit elemeztük. Eredmények: Megállapítottuk, hogy betegeink a cardiovascularis betegségek terén egészségtudatosak, daganatok miatt végzett szűrővizsgálatokon behívásra részt vesznek, azonban melanomával kapcsolatos ismereteik hiányosak. Önvizsgál… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…most of them perform skin self-examination, but they did not know what to check, lesion was detected mostly by the patients themselves, but it took more than one year to consult a doctor. Our study confirmed that patients' attitude toward melanoma is an important factor influencing early detection therefore which should be introduced into the routine medical care (40). In parallel with the above mentioned efforts made by the dermatologist community in Hungary, scientific reports evaluated the epidemiology of melanoma which showed gradual transformation of the body of incident melanoma cases over time.…”
Section: Incidencesupporting
confidence: 79%
“…most of them perform skin self-examination, but they did not know what to check, lesion was detected mostly by the patients themselves, but it took more than one year to consult a doctor. Our study confirmed that patients' attitude toward melanoma is an important factor influencing early detection therefore which should be introduced into the routine medical care (40). In parallel with the above mentioned efforts made by the dermatologist community in Hungary, scientific reports evaluated the epidemiology of melanoma which showed gradual transformation of the body of incident melanoma cases over time.…”
Section: Incidencesupporting
confidence: 79%